Canine Femoral Neck Lengthening Combined with DARthroplasty to Manage Severe Canine Juvenile Hip Dysplasia: A Case Report - Petazzoni, Massimo; Dallago, Melania (VCOT Open, 2019)
Objective This study is a case description of femoral neck lengthening and dorsal acetabular rim (DAR) arthroplasty to treat severe hip luxation in a 5-month-old male Cocker Spaniel (14.3 kg) and to compare the clinical outcome with that of contralateral femoral neck excision.Study design Case report.Results Femoral head coverage improved after surgery (preoperative lateralization of the centre of the femoral head with regard to the dorsolateral acetabular rim: 10 mm; postoperative lateralization of the centre of the femoral head: –1.3 mm). The postoperative Barden's test was negative. The dog was bearing weight 2 weeks postoperatively. Radiographic signs of bone healing were present at the 6-week follow-up examination. No complications were detected.Conclusions Femoral neck lengthening and DAR augmentation were performed in a growing dog affected by severe hip luxation and DAR insufficiency.
Keywords: hip dysplasia; femoral neck lengthening; dorsal acetabular rim; arthroplasty; canine